Which Frail Older Patients Use Online Health Communities and Why? A Mixed Methods Process Evaluation of Use of the Health and Welfare Portal - Makai, Peter; Perry, Marieke; Robben, Sarah HM; Schers, Henk; Heinen, Maud; Olde Rikkert, Marcel GM; Melis, René JF (JMIR Publications, 2014)
BackgroundFrail older people often receive fragmented care from multiple providers. According to the literature, there is an urgent need for coordination of care. Online and eHealth tools are increasingly used to improve coordination. However, there are significant barriers to their implementation in frail older people. ObjectiveOur aim was to (1) evaluate differences in use of a personal online health community (POHC) for frail older people in relation to personal characteristics, and (2) explore barriers and facilitators for use as experienced by older people and their informal caregivers, using the case of the Health and Welfare Information Portal (ZWIP). MethodsThis is a mixed methods study. For the quantitative analysis, we used POHC usage information (2 years follow-up) and baseline characteristics of frail older people. For the qualitative analysis, we used semistructured interviews with older people and their informal caregivers. Participants were recruited from 11 family practices in the east of the Netherlands and frail older people over 70 years. The ZWIP intervention is a personal online health community for frail older people, their informal caregivers, and their providers. ZWIP was developed at the Geriatrics Department of Radboud University Medical Center. We collected data on POHC use for 2 years as well as relevant patient characteristics. Interview topics were description of use, reasons for use and non-use, and user profiles. ResultsOf 622 frail patients in the intervention group, 290 were connected to ZWIP; 79 used ZWIP regularly (at least monthly). Main predictors for use were having an informal caregiver, having problems with activities of daily living, and having a large number of providers. Family practice level predictors were being located in a village, and whether the family practitioners had previously used electronic consultation and cared for a large percentage of frail older people. From 23 interviews, main reasons for use were perceiving ZWIP to be a good, quick, and easy way of communicating with providers and the presence of active health problems. Important reasons for non-use were lack of computer skills and preferring traditional means of consultation. ConclusionsOnly 27.2% (79/290) of frail older enrolled in the POHC intervention used the POHC frequently. For implementation of personal online health communities, older people with active health problems and a sizable number of health care providers should be targeted, and the informal caregiver, if present, should be involved in the implementation process. Trial RegistrationInternational Standard Randomized Controlled Trial Number (ISRCTN): 11165483; http://www.controlled-trials.com/isrctn/pf/11165483 (Archived by WebCite at http://www.webcitation.org/6U3fZovoU).